THE EFFECT OF ADDING ANDESITE MASS FRACTION TO ALUMINUM MATRIX COMPOSITES ON WEAR, HARDNESS, AND MICROSTRUCTURES - Santoso, Budi; Suprapto, Wahyono; Irawan , Yudy Surya; Thanigaivelan, R. (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
This study analyzes the effect of adding andesite mass fraction on the mechanical properties of Aluminum Matrix Composite (AMC), especially hardness, wear rate, and microstructures, to develop AMC with new reinforcement. The test results show that increasing the andesite mass fraction increases the hardness of AMC, with the highest average hardness value reaching 96.0 HRB in Al-Zn-7.5% Andesite variation. In contrast, the variation without andesite addition showed the lowest hardness of 74.8 HRB. The microstructures analysis showed an even distribution of andesite particles, which contributed to the increase in hardness and indicated good material homogeneity. Nonetheless, the increase in porosity in Al-Zn-10% Andesite variation affected a decrease in hardness and wear rate, noting the importance of control over such factors in developing AMCs for applications requiring high mechanical resistance. This study provides a reference for AMC development on optimizing the composite material composition to achieve an optimal balance between hardness and wear resistance.